PENGARUH INFLASI, RETURN PASAR, DAN PRICE EARNING RATIO TERHADAP RETURN SAHAM - Waskito, Bima Satriya; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Indicators of micro and macro economy have influence to the capital market in general and stocks inparticular. The indicator of macro economy e.g. inflation has negative influence to the stock return, the conditionof stock market, condition of stock market or market return has positive influence to the stock return. Theindicator of micro economy for instance, Price Earnings Ratio (PER) has positive influence to the stock return.This research studies about the influence of indicators of macro and micro economy i.e. inflation rates, marketreturn, and Price Earnings Ratio (PER) to the stock return at LQ45 Companies which are listed in IndonesiaStock Exchange (IDX). This research applies secondary data. The sample collection has been done by usingpurposive sampling method. The sample has been done by using seventeen LQ45 companies in 2012-2014periods. The data has been retrieved from Journal of Bank Indonesia, Financial Economics Statistics Indonesia(SEKI) and IDX Monthly Statistics. The analysis technique has been done by using multiple linear regressionsanalysis. The result of this research shows that inflation (LIF) has significant and negative influence to the stockreturn. Meanwhile, Price Earnings Ratio (PER) does not have any significant but positive influence to the stockreturn.Keywords: Inflation (ILF), Market Return (REP), Price Earning Ratio (PER), Stock Return.